Stability, electronic structures and thermoelectric properties of binary Zn–Sb materials. Issue 47 (21st November 2016) - He, Xin; Fu, Yuhao; Singh, David J.; Zhang, Lijun
Abstract : The composition–structure–property relationship of a complex high-performance thermoelectric system, Zn–Sb compounds, is systemically investigated by first-principles calculations. Abstract : We report first principles studies of the binary Zn–Sb phases in relation to thermoelectric properties and chemical stability. We identify the unknown structure of the Zn3 Sb2 phase using particle swarm optimization, finding a tetragonal structure different from the hexagonal Mg3 Sb2 and the hexagonal or cubic Ca3 Sb2 phases. All the phases are found to be semiconducting with bandgaps in the range of 0.06–0.77 eV. This semiconducting behavior is understood in Zintl terms as a balance between the Zn : Sb and Sb 3−  : ½(Sb2 ) 4− ratios in the stable crystal structures. With the exception of Zn3 Sb2, which has a small gap, all the compounds have electronic properties favorable for thermoelectric performance.